Biogenic zinc nanoparticles from weeds as an innovative zinc source for boosting growth, yield, and profitability in maize - Nayak, Parthivi; Jayadeva H M; Sannagoudar, Manjanagouda S.; Somashekharappa P R; Kurdekar, Akshay Kumar; Kadalli G G; George, Anjitha; Shantharaja C S; Sripathy K V; Rajanna G A; Paramesh V; Halli, Hanamant M.; et al. (Frontiers in Sustainable Food Systems, 2025)
Nanotechnology offers a sustainable strategy for improving nutrient efficiency and crop productivity. This study hypothesized that green-synthesized zinc oxide nanoparticles (Zinc based NPs), derived from weed leaf extracts, could enhance maize performance more effectively than conventional zinc sources. Zinc based NPs (76.89 nm, spherical) were synthesized and characterized, then evaluated through a field experiment using maize hybrid MAH 14–5. Treatments involved seed priming with 800 ppm zinc-based NPs and foliar applications at 200–600 ppm under a randomized complete block design. Results revealed that the combination of seed priming and 500 ppm foliar spray (T5) significantly improved plant height (277.6 cm), leaf area index (2.99), and dry matter production (344 g plant−1). This treatment also recorded the highest kernel yield (8,525 kg ha−1), stover yield (11,803 kg ha−1), and harvest index (0.422), outperforming conventional ZnSO4 treatments. These findings suggest that biogenic nano zinc is a promising, eco-friendly alternative for boosting maize yield and resource use efficiency.